Seismic imaging of reservoir flow properties: Resolving waterinflux and reservoir permeability - Vasco, D.W.; Keers, Henk (Lawrence Berkeley National Laboratory, 2006)
Methods for geophysical model assessment, in particuale thecomputation of model parameter resolution, indicate the value and thelimitations of time-lapse data in estimating reservoir flow properties. Atrajectory-based method for computing sensitivities provides an effectivemeans to compute model parameter resolutions. We examine the commonsituation in which water encroaches into a resrvoir from below, as due tothe upward movement of an oil-water contact. Using straight-forwardtechniques we find that, by inclusing reflections off the top and bottomof a reservoir tens of meters thick, we can infer reservoir permeabilitybased upon time-lapse data. We find that, for the caseof water influxfrom below, using multiple time-lapse 'snapshots' does not necessarilyimprove the resolution of reservoir permeability. An application totime-lapse data from the Norne field illustrates that we can resolve thepermeability near a producing well using reflections from threeinterfaces associated with the reservoir.